A Preliminary Investigation into the Neural Correlates of Knee Loading during a Change of Direction Task in Individuals after Anterior Cruciate Ligament Reconstruction - Adam Culiver; Dustin Grooms; Nathan Edwards; Laura Schmitt; James Oñate (North American Sports Medicine Institute, 2023)
# Background Central nervous system (CNS) function after ACLR, quantified by the blood oxygen level dependent (BOLD) response, is altered in regions of sensory function during knee movement after ACLR. However, it is unknown how this altered neural response may manifest in knee loading and response to sensory perturbations during sport specific movements. # Purpose To investigate the relationship among CNS function and lower extremity kinetics, under multiple visual conditions, during 180° change of direction task in individuals with a history of ACLR. # Methods Eight participants, 39.3 ± 37.1 months after primary, left ACLR performed repetitive active knee flexion and extension of their involved knee during fMRI scanning. Participants separately performed 3D motion capture analysis of a 180° change of direction task under full vision (FV) and stroboscopic vision (SV) conditions. A neural correlate analysis was performed to associate BOLD signal to knee loading of the left lower extremity. # Results Involved limb peak internal knee extension moment (pKEM) was significantly lower in the SV condition (1.89 ± 0.37 N\*m/Kg) compared to the FV condition (2.0 ± 0.34 N\*m/Kg) (p = .018). Involved limb pKEM during the SV condition was positively correlated with BOLD signal in the contralateral precuneus and superior parietal lobe (Voxels: 53; p = .017; z-stat max: 6.47; MNI peak: 6, -50, 66). # Conclusion There is a positive association between involved limb pKEM in the SV condition and BOLD response in areas of visual-sensory integration. Activation of contralateral precuneus and superior parietal lobe brain regions may be a strategy to maintain joint loading when vision is perturbed. # Level of Evidence Level 3